Promotional Tools Effect on Pharmaceuticals Marketing - Pokharel, Post Raj (Saptagandaki Journal, 2017)
This paper shows the effect of promotional tools on pharmaceuticals marketing. The study is based on survey method using marketing field force and their opinion in relation to the promotional tools used in pharmaceuticals marketing. This study which is primarily descriptive focuses on finding out tools used as promotional devices and their significance on marketing. The study shows that doctors detailing is the most effective tools used as promotional tool and has most significant effect on marketing. Use of product sample has also significant effect on marketing subsequent to the doctors detailing. In addition to that, pharmaceuticals' marketing has been positively influenced by the corporate presence in different health related activities like CME programs, health camps where multiple promotional effects have been made. CME programs and health camps tools have been more successful in effective marketing especially on specialty products like: anti-diabetics, anti-psychiatric, and cardiac products etc. The Saptagandaki Journal Vol.8 2017: 79-84